2020
DOI: 10.3390/ijms21176314
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Adaptive IRE1α Signaling and PLK2 in Multiple Myeloma: Possible Anti-Tumor Mechanisms of KIRA8 and Nilotinib

Abstract: Background: Inositol-requiring enzyme 1α (IRE1α), along with protein kinase R-like endoplasmic reticulum kinase (PERK), is a principal regulator of the unfolded protein response (UPR). Recently, the ‘mono’-specific IRE1α inhibitor, kinase-inhibiting RNase attenuator 6 (KIRA6), demonstrated a promising effect against multiple myeloma (MM). Side-stepping the clinical translation, a detailed UPR phenotype in patients with MM and the mechanisms of how KIRA8 works in MM remains unclear. Methods: We characterized UP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Moreover, the disruption of the IRE1a-XBP1s axis was shown to reduce the viability and drug resistance of MM cells in different contexts [17][18][19]. For example, anti-IRE1a drugs, such as nilotinib and KIRA8, showed beneficial effects against MM in synergy with bortezomib and lenalidomide [20]. On the other hand, it is known that IREa-XBP1s can regulate protumor environment acting also in non-tumor cells such as osteoclasts and BMMSCs [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the disruption of the IRE1a-XBP1s axis was shown to reduce the viability and drug resistance of MM cells in different contexts [17][18][19]. For example, anti-IRE1a drugs, such as nilotinib and KIRA8, showed beneficial effects against MM in synergy with bortezomib and lenalidomide [20]. On the other hand, it is known that IREa-XBP1s can regulate protumor environment acting also in non-tumor cells such as osteoclasts and BMMSCs [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…These events lead to the resolution of ER stress, reached with a reduction in mRNA translation and protein folding, as well as to cell survival. It is not surprising that this pathway, in particular the IRE1a-XBP1s axis, is activated in MM cells to avoid apoptosis caused by ER stress, due to abnormal IgG production, and that it is involved in MM chemoresistance [17][18][19][20]. Previous publications showed that the inhibition or disruption of the IRE1a-XBP1s axis in MM cells can reduce tumor progression [17][18][19] and can synergize with MM-specific drugs such as bortezomib and lenalidomide [17,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, interference with PLK2 might lead to the loss of interaction with miR-101-3p target gene SKP1, and the accumulation of cotransfected overexpressed α-Syn protein due to decreased ubiquitination degradation, leading to ER stress of neurons, suggesting that PLK2 could prevent ER stress ( 28 ). PLK2 is hyper-expressed in multiple myeloma (MM) patients; PLK2 further inhibits C/EBP homologous protein (CHOP) and enhances inositol-requiring enzyme 1α (IRE1α) by inhibiting KIRA8 (kinase-inhibiting RNase attenuator 8), which in turn affects ER stress and facilitates cell survival; Meanwhile, KIRA8/IRE1α could reversely regulate PLK2 expression; KIRA8 and PLK2 inhibitors exert anti-MM effects by inducing apoptosis and regulating cell proliferation ( 81 ). In ER stress induced by Brefeldin A (BFA), increased binding of CHOP to the PLK2 promoter C/EBPα response element results in downregulation of PLK2 expression; Overexpression of exogenous PLK2 could inhibit cell apoptosis and promote cell proliferation ( 82 ).…”
Section: Role Of Plk2 In Basic Pathophysiological Processesmentioning
confidence: 99%
“…Like its compatriots, the role of PLK2 in tumor has attracted considerable attention. Although it is reported that PLK2 is highly expressed in MM and facilitates tumor cell vitality by inhibiting KIRA8 induced CHOP mediated apoptosis ( 81 ), more studies have showed PLK2 acts as a tumor suppressor in hematological neoplasma. In B-cell lymphoma ( 26 ), acute myelogenous leukemia (AML) and myelodysplastic syndromes (MDS) ( 90 ), remarkable reduction of PLK2 expression might be related to abnormal methylation.…”
Section: Role Of Plk2 In Diseasesmentioning
confidence: 99%